2020
DOI: 10.1111/nph.16828
|View full text |Cite
|
Sign up to set email alerts
|

A basic/helix–loop–helix transcription factor controls leaf shape by regulating auxin signaling in apple

Abstract: Climate-driven phenological change across local spatial gradients leads to leaf shape variation. At higher elevations, leaves of broadleaf species tend to become narrower, but the underlying molecular mechanism is largely unknown. In this study, a series of morphometric analyses and biochemical assays, combined with functional identification in apple, were performed. We show that the decrease in apple leaf width with increasing altitude is controlled by a basic/helix-loop-helix transcription factor (bHLH TF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…In maize, ZmPIN1a has been reported to regulate auxin spatiotemporal asymmetric distribution in multiple plant developmental processes (Li et al, 2018). Suppressing apple auxin efflux carrier MdPIN1 has an impact on leaf shape (Hu et al, 2020). A recent study in Nymphaea colorata showed that PIN1, PIN3, and PIN7 are involved in the regulatory network of flower development (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In maize, ZmPIN1a has been reported to regulate auxin spatiotemporal asymmetric distribution in multiple plant developmental processes (Li et al, 2018). Suppressing apple auxin efflux carrier MdPIN1 has an impact on leaf shape (Hu et al, 2020). A recent study in Nymphaea colorata showed that PIN1, PIN3, and PIN7 are involved in the regulatory network of flower development (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The MdActin (GenBank accession number CN938024) was used as the internal control. Quantitative analysis of gene expression was performed based on the 2 -∆∆CT method [ 69 ]. Specific primers of the MdCYPs gene were designed and listed in Supplementary Table 4 .…”
Section: Methodsmentioning
confidence: 99%
“…An apple basic/helix–loop–helix transcription factor MdbHLH3 is expressed at a higher level at a higher altitude. It controls leaf shape by specifically activating auxin amido conjugate synthase gene MdGH3-2 and suppressing pin-formed auxin efflux transporter gene MdPIN1 [ 54 ]. The NAC transcription factor VviNAC33 of grapevine ( Vitis vinifera L.) is a negative regulator of the auxin pathway.…”
Section: The Roles Of Auxin In Vegetative Growth Of Horticultural Plantsmentioning
confidence: 99%